477 Oligosaccharide and IgG concentrations throughout the first week of lactation in multiparous and primiparous Holstein dairy cattle. (7th December 2018) - Fischer, A; Hertogs, K; Hatew-Chuko, B; Steele, M
Abstract: Colostrum and milk oligosaccharides (OS) can function as prebiotic substances, inhibit pathogenic organisms, and may enhance the uptake of IgG in the small intestine. The objective of this study was to characterize the OS profile during the first week of lactation in primiparous and multiparous Holstein dairy cattle. The experiment was conducted on a commercial dairy farm in Alberta, where multiparous (n=10, MP) and primiparous (n=10, PP) dairy cows were assigned to the study at the time of calving. The colostrum sample was taken within 12h after calving, followed by collection of milkings 2–6, 8, 10, 12 and 14. Samples were analyzed for concentrations of 3'sialyllactose (3'SL), 6'sialyllactose (6'SL), 3'sialyllactosamine (3'SLN), 6'sialyllactosamine (6'SLN) and disialyllactose (DSL) using a liquid chromatography-mass spectrometry system and for IgG concentrations using radial immunodiffusion. Data were analyzed using PROC MIXED (SAS 9.4) with milking and parity as a fixed effect and animal within parity as random effect. Concentrations of IgG were highest ( P <0.0001) in colostrum and milking 2 compared to all other milkings. Moreover, PP animals (82.1 ± 3.14 mg/ml) had lower ( P =0.03) concentrations of IgG compared to MP animals (106.1 ± 16.18 mg/ml) in colostrum. In regards to OS concentrations, 3'SL, 6'SL and 6'SLN were higher ( P <0.0001) in colostrum and milking 2 compared to all other milkings, where as DSL was only different ( P <0.0001) in colostrum. As expected, 3'SL was the most abundant ( P <0.0001) OS in colostrum and milking 2 and 3'SLN was only detected in trace amounts. Differences among parity were detected for 6'SLN in colostrum, with PP animals having lower concentrations ( P =0.08, 61.3 ± 23.13 μg/ml vs. 127.1 ± 23.6 μg/ml) compared to MP animals. These findings demonstrate that feeding milking 2 (transition milk) to newborn calves may have significant benefits in establishing a healthy gut bacterial community and immune system.